2013
DOI: 10.1183/09031936.00112412
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor subtype-specific effects on cigarette smoke-induced inflammation in mice

Abstract: Cholinergic tone contributes to airflow obstruction in chronic obstructive pulmonary disease. Accordingly, anticholinergics are effective bronchodilators by blocking the muscarinic M 3 receptor on airway smooth muscle. Recent evidence indicates that acetylcholine also contributes to airway inflammation. However, which muscarinic receptor subtype(s) regulates this process is unknown.In this study, the contribution of the M 1 , M 2 and M 3 receptor subtypes to cigarette smoke-induced airway inflammation was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 44 publications
5
39
0
Order By: Relevance
“…This aligns well with the reduction in TGF-β we have previously found in muscarinic M 3 receptor knock-out mice [8], and with the human data from the UPLIFT (Understanding Potential Long-term Impacts on Function with Tiotropium) trial, where tiotropium reduced lung function decline in a subgroup of patients [11].…”
Section: Anti-inflammatory Effects Of Targeted Lung Denervation In Pasupporting
confidence: 68%
See 1 more Smart Citation
“…This aligns well with the reduction in TGF-β we have previously found in muscarinic M 3 receptor knock-out mice [8], and with the human data from the UPLIFT (Understanding Potential Long-term Impacts on Function with Tiotropium) trial, where tiotropium reduced lung function decline in a subgroup of patients [11].…”
Section: Anti-inflammatory Effects Of Targeted Lung Denervation In Pasupporting
confidence: 68%
“…It has been shown that lipopolysaccharide-induced and cigarette smoke-induced inflammation and remodelling can be inhibited by anticholinergic treatment or by knock-out of the muscarinic M 3 receptor [7,8].…”
Section: Anti-inflammatory Effects Of Targeted Lung Denervation In Pamentioning
confidence: 99%
“…Therefore, impaired clearance of detrimental smoke particles from the airways after knock out of the M 1 receptor could underlie the enhanced inflammatory response observed in M 1 R -/-animals. This is further supported by a marked induction in the release of the cytokines IL-6 and monocyte chemoattractant protein-1 (MCP-1) in M 1 R -/-animals compared with wildtype animals [23] (Figure 1). …”
Section: Copdmentioning
confidence: 81%
“…This is important from a therapeutic perspective, because it would imply that prevention of bronchoconstriction might prevent airway remodeling in asthma. However, it seems unlikely that the entire anti-inflammatory and remodeling activity of anticholinergics is due to these biomechanical effects, as in the above mentioned studies bronchoconstriction was selectively coupled to remodeling, and not to inflammation, whereas anticholinergics and M 3 receptor knockout have clear anti-inflammatory effects on neutrophilic inflammation [4,23]. Moreover, over the past decades, it has become clear that acetylcholine is not only released as a neurotransmitter from nerve terminals, but also as a hormone from non-neuronal cells, including epithelial cells and inflammatory cells, acting in an autocrine and/or paracrine manner [2,14].…”
Section: Bronchoconstriction As a Driver Of Airway Remodelingmentioning
confidence: 92%
See 1 more Smart Citation